Strategies to Increase Income for Semi-technical Irrigated Rice Farming in Pengandonan Subdistrict, Pengandonan District, Ogan Komering Ulu - Supriyanto, Supriyanto; Munajat, Munajat; Sari, Yunita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Rice farming is one of the production activities in agriculture carried out by farmers, including those carried out by farmers in the Pengandonan district of Ogan Komering Ulu regency. Farmers run their Rice farming business to get their family's source of income to meet the needs of life and improve the level of welfare of farmers. This study aims to determine the amount of income for half-technical irrigated Rice farming and determine the strategy of increasing the income of half-technical irrigated Rice farming in the Pengandonan District. The research was carried out in Pengandonan District, Ogan Komering Ulu regency, which was carried out from March to July 2022 using survey and interview methods and filling out questionnaires. The data collected are primary and secondary. The sampling technique uses a simple random method on a sample of farmers as respondents where the number of farmers is determined by the solving method. The data analysis method uses R/C ratio analysis and SWOT analysis by considering internal factors or IFAS (Internal Factor Analysis Strategic) and external factors or EFAS (External Factor Analysis Strategic). The results showed that the half-technical irrigated rice farming business in the Pengandonan sub-district is profitable with an R/C ratio of 2.8 and the strategy of increasing the income of half-technical irrigated Rice farming in the Pengandonan sub-district is a diversification strategy, namely by utilizing the high motivation of farmers by participating in the AUTP (Rice Anticipation Insurance) program as a crop failure due to pest and disease attacks, always optimize the adoption rate of technology as well as involve more labor in the family in farming activities, increase the intensity of meetings with agricultural officials in overcoming pest and disease attacks, and optimize land conditions by improving irrigation systems.